2022
DOI: 10.3390/jcm11247310
|View full text |Cite
|
Sign up to set email alerts
|

A Novel PiRNA Enhances CA19-9 Sensitivity for Pancreatic Cancer Identification by Liquid Biopsy

Abstract: Pancreatic cancer is one of the deadliest tumours worldwide, and its poor prognosis is due to an inability to detect the disease at the early stages, thereby creating an urgent need to develop non-invasive biomarkers. P-element–induced wimpy testis (PIWI) proteins work together with piwi-interacting RNAs (piRNAs) to perform epigenetic regulation and as such hold great potential as biomarkers for pancreatic cancer. PIWIL2 and PIWIL4 are associated with better prognosis, while PIWIL1 and PIWIL3 involvement appea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…PIWIL1 inhibits the invasion and migration abilities of pancreatic stellate cells through the PI3K/AKT/mTOR signaling pathway (21). It also appears to be involved in the carcinogenesis of pancreatic cancer (22). Knockdown of PIWIL1 could inhibit cell proliferation and induce apoptosis in glioma cells (23).…”
Section: Discussionmentioning
confidence: 99%
“…PIWIL1 inhibits the invasion and migration abilities of pancreatic stellate cells through the PI3K/AKT/mTOR signaling pathway (21). It also appears to be involved in the carcinogenesis of pancreatic cancer (22). Knockdown of PIWIL1 could inhibit cell proliferation and induce apoptosis in glioma cells (23).…”
Section: Discussionmentioning
confidence: 99%
“…Although there are a lot of reports about the various biological functions of piRNAs in occurrence and development of cancer [17][18][19][20], the relationship between piRNAs and CC is not well known. It has been shown that piRNA-36712 was low expressed in breast cancer than in matched controls and its overexpression restrains progression and chemoresistance of CC cells by interacting with SEPW1P RNAs [21]. By piRNA expression profile analysis, Bartos et al report that piRNA-9491 and piRNA-12488 were significantly dysregulated in glioblastoma cells and could reduce the ability to form colonies in vitro [17].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there are several signal transduction pathways and related factors that regulate human trophoblast invasion/migration, such as the mitogen-activated protein kinase (MAPK) signaling pathway [ 87 89 ]、Wnt signaling pathway [ 90 92 ] and matrix metalloproteinases (MMPs) [ 93 , 94 ] which are associated with the impaired remodeling of spiral arteries and are regulated by the complementary binding of piRNAs [ 95 97 ]. For example, piR-63049 has a 7 nt putative binding site containing for Wnt2B 3'-UTR, which negatively regulates Wnt/β-catenin pathway activity by inhibiting the expression of Wnt2B, a highly conserved member of the Wnt family, thereby inhibiting osteoclastogenesis in bone marrow stromal cells [ 98 ].…”
Section: Pirnas: Potential Epigenetic Regulators Of Pe Pathogenesismentioning
confidence: 99%